A New Class of q-Fibonacci Polynomials - Cigler, Johann (The Electronic Journal of Combinatorics, 2003)
We introduce a new q-analogue of the Fibonacci polynomials and derive some of its properties. Extra attention is paid to a special case which has some interesting connections with Euler’s pentagonal number theorem.